Hydrogel associated with soil moisture levels in the cultivation of Eucalyptus urograndis - Silva, Jonas Santos; Braulio, Caliane da Silva; de Jesus, Daiana Souza; Leite, Elton da Silva; Nóbrega, Rafaela Simão Abrahão; Martins, Ricardo Previdente [UNESP]; Nóbrega, Júlio César Azevedo (Universidade Federal de Santa Maria, 2024)
Although technological advances have occurred in the Brazilian forestry sector, there is still no standardization for the cultivation of Eucalyptus urograndis regarding the amount of water which needs to be applied at different stages of plant development and the doses of soil moisture conditioners to reduce the water deficit in the soil. The objective of this study was to evaluate the use of hydrogels for their association with soil moisture levels in regard to Eucalyptus urograndis. This study was conducted in a greenhouse at the Federal University of Reconcavo, Bahia. The treatments consisted of four levels of soil moisture (50, 75, 100%, and 125%) and four doses of the available hydrogel (0, 1.5, 3.0 and 4.5 g L-1) in a randomized design in a 4 × 4 factorial scheme with 16 treatments and four replicates. The evaluated parameters were height (H), stem diameter (SD), chlorophyll A and B, total indices, stem dry mass (SDM), leaf dry mass (DML), shoot dry mass (SSDM), root dry mass (RDM), shoot dry mass/ root dry mass (SSDM/RDM), total dry mass (TDM), and height/diameter (H/SD). The use of hydrogels increased water availability in the dystrocohesive Yellow Oxisol and reduced the effect of water deficit in Eucalyptus urograndis. A dose of 3.0 g L-1 of the hydrogel provided better growth and phytomass production in regard to Eucalyptus urograndis when the initial soil moisture level was approximately field capacity.
Hidrogel associado a níveis de umidade do solo no cultivo de Eucalyptus urograndis
Keywords: Dystrocohesive Yellow Oxisol; Hydrogel doses; Water deficit